Ursodeoxycholic acid relieves clinical severity of COVID-19 in patients with chronic liver diseases - Hu, Tiantian; Tong, Jie; Yang, Yunhui; Yuan, Changrong; Zhang, Jiming; Wang, Jinyu (Frontiers in Medicine, 2025)
BackgroundThe potential effect of ursodeoxycholic acid (UDCA) on the clinical outcomes of SARS-CoV-2 in patients with chronic liver diseases has been a subject of ongoing debate since the onset of the SARS-CoV-2 pandemic in 2019. This study aims to investigate the effect of UDCA on the prognosis of SARS-CoV-2 infection in patients with chronic liver diseases.MethodsA total of 926 patients with chronic liver diseases who contracted their first SARS-CoV-2 infection during December 2022 to January 2023, were included in this study. Participants were divided into two groups based on the use of UDCA: the UDCA cohort (n = 329) and the non-UDCA cohort (n = 597). After performing a 1:1 age-and sex-matching, the analysis proceeded with 309 patients from each group for further evaluation.ResultsIn the UDCA-treated cohort, the incidence of asymptomatic SARS-CoV-2 infections was significantly higher, with 30.1% of patients affected, compared to 6.47% in the non-UDCA group (p < 0.0001). Multivariable analysis identified UDCA as a protective factor against symptomatic infections, yielding an odds ratio (OR) of 4.77 (95% CI: 2.70–8.44, p < 0.001). Furthermore, age over 50 was found to be a risk factor for asymptomatic infections in the UDCA cohort, with an adjusted OR of 1.51 (95% CI: 1.01–2.24, p = 0.05).ConclusionThe study suggests that UDCA therapy may improve clinical outcomes in patients with chronic liver diseases patients who are infected with SARS-CoV-2, highlighting its potential role in improving prognosis within this vulnerable population. However, further research is required to validate these findings and to elucidate the mechanisms underlying UDCA’s protective effect.